On the Locating Chromatic Number of Barbell Shadow Path Graph - A. Asmiati; Maharani Damayanti; Lyra Yulianti (Indonesian Combinatorial Society (InaCombS), 2021)
The locating-chromatic number was introduced by Chartrand in 2002. The locating chromatic number of a graph is a combined concept between the coloring and partition dimension of a graph. The locating chromatic number of a graph is defined as the cardinality of the minimum color classes of the graph. In this paper, we discuss about the locating-chromatic number of shadow path graph and barbell graph containing shadow graph.